Hans Seybolt's news about the Bosnian king Nicholas of Ilok and his son Lawrence from 1476 - Rabić, Nedim (Historical Thought, 2025)
Hans Seybolt was a monastery scribe from Lower Bavaria who lived in the second half of the 15th century. In 1476, he attended the wedding between the Hungarian king Matthias Corvinus and the Neapolitan princess Beatrix as an envoy of the count of the Palatinate. He left a detailed report about that event, which is preserved as a transcript in the only copy that is in the State Library of Bavaria under the signature Cgm 331. Seybolt's report also contains brief information about the Bosnian king Nicholas of Ilok and his son Lawrence, which are the subject of this paper's analysis.